Clinical characteristics associated with therapeutic nonadherence of the patients with major depressive disorder: A report on the National Survey on Symptomatology of Depression in China. (11th July 2018) - Zhou, Qian; Wu, Zhi‐Guo; Wang, Yun; Liu, Xiao‐Hua; Chen, Jun; Wang, Yong; Su, You‐Song; Zhang, Chen; Peng, Dai‐Hui; Hong, Wu; Fang, Yi‐Ru
Summary: Aims: Nonadherence is one of the leading challenges to treatment of the major depressive disorder (MDD). Few studies have systematically analyzed the relationship between clinical characteristics, especially symptoms of depressive patients and their therapeutic nonadherence over a relatively large sample. This study aimed to investigate factors of nonadherence in a nationwide survey in China. Methods: Participants with MDD who met the criteria of Diagnostic and Statistical Manual of Mental Disorders (Fourth Edition) (DSM‐IV) were recruited from 32 sites throughout China. Patients were all over 16 years old. A doctor‐rating questionnaire with 64 symptoms based on DSM‐IV was constructed to evaluate depression‐related feeling and behavior. Single‐factor logistic regression was utilized to screen variables, and multifactor logistic regressive analysis was used to identify which factors were risk or protective for nonadherence. We included 882 patients of poor adherence and 857 patients of good adherence. Results: Recurrence, untreated first episode, tricyclic antidepressant (TCA)‐treated first episode, antidepressant‐only‐treated current episode, decrease or loss of interest, more somatic symptoms, and "atypical" symptoms were risk factors for nonadherence, whereas selective noradrenaline reuptake inhibitor (SNRI)‐treated first episode was a protecting factor. Conclusion: Clinical characteristics may play an important role in predicting nonadherence. Doctors may have to pay much attention on patients with these factors and should keep on discussing them with patients.